47.2k views
1 vote
2(-x-4)+3=-7x+5+5x

Pls help!!!!!!!!

User William R
by
5.8k points

2 Answers

6 votes

1 Simplify

7
x
+
5
+
5
x
−7x+5+5x to

2
x
+
5
−2x+5.
2
(

x

4
)
+
3
=

2
x
+
5
2(−x−4)+3=−2x+5

2 Expand.

2
x

8
+
3
=

2
x
+
5
−2x−8+3=−2x+5

3 Simplify

2
x

8
+
3
−2x−8+3 to

2
x

5
−2x−5.

2
x

5
=

2
x
+
5
−2x−5=−2x+5

4 Cancel

2
x
−2x on both sides.

5
=
5
−5=5

5 Since

5
=
5
−5=5 is false, there is no solution.
No Solution
User Lisaann
by
4.4k points
4 votes
4 I hope this helps you
User Nandhini
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.